Investigations of thermal conductivity of simple van der Waals crystal-based nanocomposites - Nikonkov, R.V.; Stachowiak, P.; Romanova, T.V.; Jeżowski, A.; Sumarokov, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
The experimental setup for obtaining and determination of the thermal conductivity of simple van der Waals crystal-based nanocomposites is described. Preliminary thermal conductivity results of measurements carried out in the temperature range 1–40 K on two samples of methane crystals containing nanoparticles of hydroxyapatite are presented. These results confirm usability of the setup and its suitability as a proper experimental method for investigations of the thermal conductivity of the nanocomposites.